Intergenerational Allocation of Government Expenditures : Externalities and Optimal Taxation - Iqbal, Kazi (2012)
This paper studies optimal capital and labor income taxes when the benefits of public goods are age-dependent. Provided the government can impose a consumption tax, it can attain the first-best resource allocation. This involves the uniform taxation of the cohorts' labor income and a zero capital income tax. With no consumption tax and optimally chosen government spending, labor income should be taxed nonuniformly across cohorts and the capital income tax should be nonzero. Deviations of the public goods from their respective optima create distortions. These affect the labor supply decisions of both cohorts and capital accumulation, providing a further reason to tax (or subsidize) capital income.